Interaction study of monoisoamyl dimercaptosuccinic acid with bovine serum albumin using biophysical and molecular docking approaches - Ashima Thakur (Nature Portfolio, 2021)
Abstract Monoisoamyl 2,3-dimercaptosuccinic acid (MiADMSA), a lipophilic chelator has been evaluated for its potential use as an antidote in arsenic poisoning. The pharmacokinetics and pharmacodynamics properties of a drug could be understood via study its mechanism of interaction with bovine serum albumin protein (BSA). Therefore, the interaction between MiADMSA with BSA was investigated using various spectroscopic techniques and computational methods. Linear quenching of BSA intrinsic fluorescence intensity with the increasing concentration of MiADMSA was observed in the fluorescence study. Furthermore, synchronous results revealed that MiADMSA slightly changed the conformation of BSA. The binding constant value of the BSA-MiADMSA complex was found 1.60 × 104 M−1 at 298 K. The value of thermodynamic parameters ΔG, ΔH, and ΔS described that the process is spontaneous, endothermic, and hydrophobic forces are involved in the interaction of MiADMSA with BSA. Competitive site marker experiments showed that MiADMSA binds to site-II of BSA. Conformational changes of BSA with the interaction of MiADMSA were apparent by CD, UV–Visible, FT-IR, and 3D fluorescence spectroscopy. To strengthen the experimental findings we have also performed a theoretical study on the BSA-MiADMSA complex. Two sites were identified with docking score of − 6.642 kcal/mol at site IIa and − 3.80 kcal/mol for site IIb via molecular docking study. Molecular dynamics simulation study inferred the stability of the BSA-MiADMSA complex which was analyzed in a long simulation run. The experimental and computational studies have shown the effective binding of MiADMSA with BSA which is essential for the transportation and elimination of a drug from the body.